Determinants of the capital structure of Portuguese firms with investments in Angola - Jorge H.F. Mota; Antonio C. Moreira (South African Journal of Economic and Management Sciences, 2017)
Background: This article seeks to complement the previous literature and clarify the particularities of the capital structure policy of firms with foreign direct investment in Angola.